Tata Kelola Teknologi Dalam Perencanaan Sektor Publik - Yuliar, Sony (Center for Research and Community Services ITB, 2008)
While in general planning concerns with social criteria and objectives, the implementation of planning often involves the introduction of new technology to regional/local communities. An important question for successful planning implementation would then be how those social criteria and objectives be integrated into technology selection process. This question leads us to a technology governance/steering problem within the context of planning. This article addresses this problem within the context of public sector planning, by arguing for a socio-technical co-evolutionary approach. By employing the notion of translation that is central in actor-network theory, a model for empirical studies is proposed. Empirical cases are presented from which normative principles for technology governance in public sector planning can be drawn.